SIFAT-SIFAT MATRIKS LUNAK FUZZY INTUISIONISTIK - Zahra Aisyananda Nokia Infaluna; Dwi Nur Yunianti (Universitas Negeri Surabaya, 2021)
Fuzzy soft sets is one of the mathematical tools that are used to deal with the problem of uncertainty, such as problems in the field of economic, health, and others. The concept of fuzzy soft sets is extended into intuitiononistic fuzzy soft sets to intuitiononistic fuzzy soft matrices. This article examines the intuitionistic fuzzy soft matrix and defines the various types and operations of the intuitionistic fuzzy soft matrix. In addition, the application of an intuitionistic fuzzy soft matrix is ​​given to decision-making problems such as the selection of swimming athletes who have the best swimming techniques.